2011
DOI: 10.1007/s00213-011-2257-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive enhancement following acute losartan in normotensive young adults

Abstract: The findings highlight a cognitive-enhancing potential for losartan on compromised cognitive systems and emphasise the potential of AIIAs to produce benefits over and above hypertension control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 61 publications
3
12
0
1
Order By: Relevance
“…Excess Ang II was linked to increased blood pressure, decreased cerebrovascular compliance and enhanced brain inflammation, all recognized risk factors for AD, while Ang II type 1 receptor (AT1R) blockade suppressed such processes [6,7]. Moreover, application of AT1R blockers to rodents led to attenuated neurotoxic accumulation and cognitive deficits [8][9][10][11][12]. In our laboratory, central infusion of Ang II significantly promoted Ab production via enhanced amyloidogenic processing [13].…”
Section: Introductionmentioning
confidence: 82%
“…Excess Ang II was linked to increased blood pressure, decreased cerebrovascular compliance and enhanced brain inflammation, all recognized risk factors for AD, while Ang II type 1 receptor (AT1R) blockade suppressed such processes [6,7]. Moreover, application of AT1R blockers to rodents led to attenuated neurotoxic accumulation and cognitive deficits [8][9][10][11][12]. In our laboratory, central infusion of Ang II significantly promoted Ab production via enhanced amyloidogenic processing [13].…”
Section: Introductionmentioning
confidence: 82%
“…Moreover, enhancing memory effects were observed in humans treated with ARBs. Losartan improved cognitive function, mainly immediate and delayed memory in elderly hypertensive humans (Fogari et al 2003 ) and in healthy young adults (Mechaeil et al 2011 ). Accumulated data unequivocally indicate the beneficial effect of ARBs in memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the medication issue, recent research suggests that angiotensin II receptor antagonists might both lower blood pressure and improve prospective remembering. Mechaeil, Gard, Jackson, and Rusted (2011) reported that an acute 50mg dose of losartan increased nonfocal prospective memory performance, though this effect was observed in normotensive younger adults. However, in a group of hypertensive older adults, Hajjar et al (2012) found that 12-months of taking 32mg of candesartan controlled blood pressure and improved executive control performance.…”
Section: Discussionmentioning
confidence: 96%